Improving care for patients with dementia hospitalized for acute somatic illness in a specialized care unit: a feasibility study - Zieschang, Tania; Dutzi, Ilona; Müller, Elke; Hestermann, Ute Marion; Grünendahl, Katinka; Bahrmann, Anke; Hüger, Daniel; Kopf, Daniel; Specht-Leible, Norbert; Oster, Peter (International psychogeriatrics, 2010)
Persons with dementia hospitalized for an acute illness have a high risk of poor outcomes and add to the burden on acute care systems. We developed a segregated Special Care Unit (SCU) in a somatic hospital for patients with challenging behavior resulting from dementia and/or delirium. This pilot study evaluates the feasibility and patient outcomes.